Deep Learning Approach in English Language Teaching: Does It Matter a Lot? - Bachtiar, Bachtiar; Zuhairi, Aminudin; Maya Puspitasari; Sylvia (LPPM ITB AAS Indonesia Surakarta, 2025)
This paper reports the outcomes of a ‘Community Service’ activity related to the implementation of the Deep Learning (DL) approach in English language teaching in Indonesia. The activity was conducted for junior high school English language teachers in Bogor regency, Indonesia. It outlines the design, implementation, and evaluation of a structured professional development program aimed at equipping teachers with the knowledge, skills, and reflective capacity needed to adopt Deep Learning within the framework of Indonesia’s Merdeka Belajar curriculum. Drawing on Michael Fullan’s 6Cs framework (i.e., character, citizenship, collaboration, communication, creativity, and critical thinking), the activity emphasized pedagogical transformation that moves beyond traditional content delivery toward student-centered, inquiry-based learning. The program adopted a four-stage model: observation, socialization, training and mentoring, and evaluation. These stages allowed facilitators to map the instructional realities of the participants, co-construct relevant training content, and evaluate the impact through both qualitative and quantitative measures. The results indicated a significant increase in teachers’ awareness of DL principles, improved pedagogical confidence, and willingness to implement more meaningful and contextualized English Language Teaching (EFL) practices. Key themes explored included the coherence between DL and the national Profil Pelajar Pancasila, strategies to overcome implementation challenges, and the integration of AI tools to enhance 21st-century competencies. The findings suggest that DL offers a transformative avenue for revitalizing ELT in Indonesia by aligning global educational innovations with local policy goals. This paper recommends sustained investment in teacher training, digital infrastructure, and curricular alignment to ensure scalable and equitable adoption of DL nationwide.